Pedagogical Anchors Amid Pedagogical Dilemmas: The Myth of Innovation and Unsustainable Expectations within Mathematics Education Research - Surur, Agus Miftakus; Pujilestari, Sri; Ridwanulloh, M. Ubaidillah (Universitas Muhammadiyah Surakarta, 2026)
Frequent curriculum changes disrupt instructional rhythms and stigmatize lecture methods, creating